Technology Refinement through on-farm trials (OFT) for wider acceptability - P.K.Singh (Journal of Agricultural Extension Management, 2025)
The transfer of research recommendations generated in experimental stations under controlled environment to real farming situation has been one of the toughest tasks of extensionists. In most of the cases the farmers reject research recommendations as they hardly solve their problems. While designing the research, researchers hardly consider the view of extension workers and farmers, which ultimately leads to rejection of recommendations